Spatiotemporal exposure of motorcyclists to particulate matter in a densely populated urban area: A case study of Varanasi, India - Behera S.K.; Mudgal A.; Singh A.K. (My University, 2025)
Researchers have studied motorcyclists' exposure to Particulate Matter (PM) during rush and non-rush hours. However, the combined effect of season and hour of the day on PM concentration has not been studied. PM concentration was measured near the typical breathing zone of motorcyclists who traveled along four designated routes in a densely populated city (Varanasi, India). Data were collected from January to June 2022 during various hours of the day (from 07:00 to 17:00 h). PM2.5 and PM10 concentration during winter was 2.36 and 1.69 times in summer, respectively. In contrast, PM2.5 and PM10 concentration during spring were 1.35 and 1.12 times during summer, respectively. PM2.5 correlated much more with relative humidity and atmospheric temperature than PM10. Higher PM concentration was recorded in rush hour (09:00–10:00) during spring and summer but in non-rush hours (12:00–13:00) during winter. The opposite trend in the winter was caused by more extended dispersion and dilution time of PM particles. Also, a higher proportion of PM2.5 was observed on routes with longer rush hours caused due to road encroachment by street vendors and pedestrians. © 2023 Turkish National Committee for Air Pollution Research and Control